Corporate Governance, Institutional Characteristics, And Director Networks In Malaysia - Jamaludin, Mohd Faizal; hashim, Fathyah (Asian Academy of Management (AAM), 2017)
This study explores the structural relationship of director networks among boards of directors in publicly listed companies in Malaysia using social network analysis (SNA) techniques at both the director and company levels. This paper examines whether company corporate governance practices and institutional characteristics are associated with company network size and pattern. SNA performed using UCINET and NetDraw software shows that the directors and company in the networking are moderately connected. This suggests that there is a small group of directors or companies that are well-connected and well-positioned to exercise power, control, and inﬂuence over the network. This study also reveals the interconnectedness of board members and companies. The regression results also identify a group of the most well-connected and well-positioned directors and companies in Malaysia’s corporate governance environment. The results suggest that board size, board meeting, and duality are the corporate governance practices, which most inﬂuence company network size and pattern. The presence of a Bumiputera or politicallyconnected director is an institutional characteristic, which especially determines the network of a company.